APPLICATION OF NANOTECHNOLOGY IN FERTILIZATION AND PLANT PROTECTION IN GERMANY - Thomas Pires; Marie Janssen; Kiril Pavlov (Techno Agriculturae Studium of Research, 2025)
Nanotechnology has emerged as an innovative solution in the agricultural sector, particularly in fertilizing and plant protection in Germany. The background of this research is the need to improve agricultural efficiency by reducing the use of chemical inputs and increasing the absorption of plant nutrients. This study aims to evaluate the impact of nanotechnology on fertilization efficiency, crop protection, and farmers' operational costs. The research uses a mixed approach, involving 200 farmers through surveys and interviews, as well as laboratory data analysis related to nutrient absorption and pesticide residues. The results showed that nanotechnology increased nutrient absorption by 25%, reduced pest attacks by up to 30%, and reduced the use of fertilizers and pesticides by up to 20%. The conclusion of this study is that nanotechnology is effective in improving agricultural technical and economic efficiency, so it has the potential to become an important component in sustainable agriculture in Germany.